A PRELIMINARY STUDY ON THE PECTORALIS BLOCK II AS A PART OF MULTIMODAL ANALGESIA FOR INTRA AND POSTOPERATIVE PAIN MANAGEMENT IN MODIFIED RADICAL MASTECTOMY - Senapathi, Tjokorda Gde Agung; Widnyana, I Made Gede; Ryalino, Christopher; Junaedi, I Made Darma (DiscoverSys Inc., 2018)
Background: Inadequate acute postoperative pain management is the main risk factor for chronic pain after breast surgery. Pectoralis blocks I and II (pecs block I and II) are novels peripheral nerves block techniques introduced since 2011 by Blanco et al.Methods: Ten patients diagnosed with breast cancer planned for modified radical mastectomy (MRM), from preoperative evaluation patients with a physical status of American Society of Anesthesiologist (ASA) I and II. Anesthesia management under general anesthesia with an endotracheal tube and we performed PECS block II after general anesthesia. We recorded the systolic blood pressure, mean arterial pressure (MAP), and heart rate intraoperatively, and the pain scale at 4th, 6th, 12th, and 24th hours postoperatively.Results: The pain scale at 4th and 6th hours postoperatively were 0.3±0.5 and 0.6±0.5 respectively. The pain scale at resting starts to increase at the 12th and 24th hours (1.2±0.4 and 1.1±0.6). The mean total use of morphine recorded on PCA was 3.3 ± 0.9 (mg). No pecs block II complications were recorded in this study.Conclusion: Pecs block II is a relatively easy, safe, and effective for MRM surgeries. Further larger and double-blinded studies are needed to know its effectiveness compared to other techniques available.